Finding Common Ground: A Critique of Subsumption Theory and Its Application to Small-Scale Forest Carbon Offsetting in Uganda. Issue 9 (2nd September 2018) - Purdon, Mark
ABSTRACT: Carbon markets as a policy tool to mitigate emissions of greenhouse gases continue to be controversial, especially in developing countries. It is thus refreshing that Carton and Andersson (2017 ) undertook a field investigation of a transnational forest carbon offset project in Uganda. However, I am concerned that assumptions of structural Marxism that underwrite subsumption theory may have led the authors to see the project as inherently conflict ridden and exploitative and to neglect actual benefits. Their presentation of the project's local impact jarred with my own empirical research into this project, undertaken in 2009, as well as more recent news accounts. While my field effort preceded the authors' by 6 years, I attribute our different interpretations largely to theoretical and methodological differences. Evidence I present below suggests considerable alignment between the interests of transnational carbon markets and Ugandan smallholder farmers. Additional fieldwork might be able to resolve these differences in interpretation.